Pidana Zina Perspektif Hukum Positif dan Hukum Islam pada Masyarakat Sumatera Barat - Yusnani, Yusnani (Universitas Islam Negeri Imam Bonjol Padang, 2017)
Enforcing norms need to criminalization, an exciting one with criminalization is watching a sex scene / cybersex impact on adultery and destroying the moral, social reality, but the rules have not been touched by the law and the Constitution. This study uses a method by ????inding the facts objectively to determine the facts that resulted in the proposition of law with normative law research empirical, which is looking for primary data directly interview to teams maker Criminal Code draft, team members Criminal Code draft and socialization to the local leaders and traditional leaders, police manuscripts / books legislation as well as academics. The conclusion: Padang city government has sought to overcome the impact of pornography negative such as additional study hours for students of religion in the mosque, and pesantren Ramadan. Especially for the closure of access to pornography has been no common ground of understanding let alone the technical implementation and enforcement of the Criminal Code Article 485 and the bill is merely the existence of a misdemeanor (plate), adultery and no single Islamic criminal law in the Marriage Law and KHI.